EXAMINATION OF APOPTOTIC CHANGES IN AROMATIC HYDROCARBON BENZENEADMINISTERED RAT TESTICULAR TISSUE WITH HISTOPATHOLOGICAL METHODS - Yildizhan, Eda; Koyutürk, Leyla Canpolat; Akkus, Murat; Tektemur, Nalan Kaya; Ozkorkmaz, Ebru Gokalp; Aşır, Fırat (My University, 2021)
Benzene is an aromatic hydrocarbon and a colorless and odorous liquid. It is used in the production of plastics, detergents, pesticides, and other chemicals. Serious deterioration is seen in sperm production of men who are exposed to hydrocarbons such as ethylbenzene, toluene, xylene, andaromatic solvents found in paints, lacquers, adhesive-like substances in their professions. The purpose of this study was to examine the possible effects of benzene on testicular tissues via histopathological and TUNEL staining methods. In this study, healthy 18 Wistar albino male rats, with a mean age of 8-10 weeks weighing 250-300 g were used. Rats were divided into 3 groups; Group I was the controlgroup. Group II was administered 1 ml/kg benzene for 9 days and Group III 1.5 ml/kg benzene for 5 days via orogastric tube. At the end of the experiment, all rats were decapitated, and their testicular tissues were excised. Stained with Haematoxylin and Eosin, Johnsen scoring was performed for each group. Apoptosis was demonstrated with TUNEL method, marked with the Image J program and statistical analysis was performed. Benzene exposed rat testicular tissues depicted thinning of seminiferous tubule epithelium cytoplasmic vacuoles, affusion of seminiferous tubule epithelium to the lumen, and affusion in spermatogenic cells (desquamation), degenerative changes in germ cells (spermatogonia), degenerative tubule structures, disorganized interstitial tissues, and absence of epithelial integrity were observed. Compared with the control group, the rats exposed to benzene revealed a significant increase in apoptotic cells in the seminiferous tubules via TUNEL staining. It was thought that exposure to benzene resulted in degeneration and increased apoptotic cells in the testicular tissues.
Keywords: Biyoloji; Patoloji; Kimya; Uygulamalı; Kimya; Tıbbi; Biyokimya ve Moleküler Biyoloji; Hücre Biyolojisi